Health interventions among mobile pastoralists: a systematic review to guide health service design. Issue 11 (21st September 2020) - Wild, Hannah; Mendonsa, Emily; Trautwein, Micah; Edwards, Jeffrey; Jowell, Ashley; GebreGiorgis Kidanu, Ashenafi; Tschopp, Rea; Barry, Michele
Abstract: Objective: Mobile pastoralists are one of the last populations to be reached by health services and are frequently missed by health campaigns. Since health interventions among pastoralists have been staged across a range of disciplines but have not yet been systematically characterised, we set out to fill this gap. Methods: We conducted a systematic search in PubMed/MEDLINE, Scopus, Embase, CINAL, Web of Science, WHO Catalog, AGRICOLA, CABI, ScIELO, Google Scholar and grey literature repositories to identify records that described health interventions, facilitators and barriers to intervention success, and factors influencing healthcare utilisation among mobile pastoralists. No date restrictions were applied. Due to the heterogeneity of reports captured in this review, data were primarily synthesised through narrative analysis. Descriptive statistical analysis was performed for data elements presented by a majority of records. Results: Our search yielded 4884 non‐duplicate records, of which 140 eligible reports were included in analysis. 89.3% of reports presented data from sub‐Saharan Africa, predominantly in East Africa (e.g. Ethiopia, 30.0%; Kenya, 17.1%). Only 24.3% of reports described an interventional study, while the remaining 75.7% described secondary data of interest on healthcare utilisation. Only two randomised controlled trials were present in our analysis, and only five reports presented data on cost. The most common facilitators of intervention success were cultural sensitivity ( n  = 16), community engagement ( n  = 12) and service mobility ( n  = 11). Conclusion: Without adaptations to account for mobile pastoralists' unique subsistence patterns and cultural context, formal health services leave pastoralists behind. Research gaps, including neglect of certain geographic regions, lack of both interventional studies and diversity of study design, and limited data on economic feasibility of interventions must be addressed to inform the design of health services capable of reaching mobile pastoralists. Pastoralist‐specific delivery strategies, such as combinations of mobile and 'temporary fixed' services informed by transhumance patterns, culturally acceptable waiting homes, community‐directed interventions and combined joint human‐animal One Health design as well as the bundling of other health services, have shown initial promise upon which future work should build. Abstract : Objectif: Les éleveurs nomades sont l'une des dernières populations à être touchées par les services de santé et sont souvent ratés par les campagnes de santé. Etant donné que les interventions de santé parmi ces éleveurs ont été programmées dans une gamme de disciplines mais n'ont pas encore été systématiquement caractérisées, nous avons entrepris de combler cette lacune. Méthodes: Nous avons effectué une recherche systématique dans les répertoires PubMed/MEDLINE, Scopus, EMBASE, CINAL, Web of Science, WHO Catalog, AGRICOLA, CABI, ScIELO, Google Scholar et de la littérature grise pour identifier les reports décrivant les interventions de santé, les facilitateurs et les obstacles au succès de l'intervention ainsi que les facteurs influençant l'utilisation des soins de santé chez les éleveurs nomades. Aucune restriction de date n'a été appliquée. En raison de l'hétérogénéité des rapports capturés dans cette revue, les données ont été principalement synthétisées au moyen d'une analyse narrative. Une analyse statistique descriptive a été effectuée pour les éléments de données présentés par une majorité des reports. Résultats: Notre recherche a révélé 4.884 rapports non dupliqués, dont 140 éligibles ont été inclus dans l'analyse. 89, 3% des rapports présentaient des données d'Afrique subsaharienne, principalement en Afrique de l'Est (ex: Ethiopie, 30, 0%; Kenya, 17, 1%). Seuls 24, 3% des rapports décrivaient une étude interventionnelle, tandis que les 75, 7% restants décrivaient des données d'intérêt secondaires sur l'utilisation des soins de santé. Seuls deux essais contrôlés randomisés étaient présents dans notre analyse, et seuls cinq rapports présentaient des données sur le coût. Les facilitateurs les plus courants du succès des interventions étaient la sensibilité culturelle (n=16), l'engagement communautaire (n=12) et la mobilité des services (n=11). Conclusion: Sans adaptations pour tenir compte des modèles de subsistance et du contexte culturel uniques des éleveurs nomades, les services de santé formels les laissent de côté. Les lacunes de la recherche, y compris la négligence de certaines régions géographiques, le manque d'études interventionnelles et la diversité de la conception des études, et les données limitées sur la faisabilité économique des interventions doivent être comblées pour éclairer la conception de services de santé capables d'atteindre les éleveurs nomades. Des stratégies de prestation spécifiques aux éleveurs nomades, telles que des combinaisons de services mobiles et «fixes temporaires» éclairés par des schémas de transhumance, des maisons d'attente culturellement acceptables, des interventions dirigées par la communauté et une conception conjointe d'une seule santé homme‐animal ainsi que le regroupement d'autres services de santé, ont montré une promesse initiale sur laquelle les travaux futurs devraient s'appuyer.